Object naming after epilepsy surgery in the dominant left temporal lobe: risk factors, time course and long-term outcome - Walther, Katrin; Reindl, Caroline; Schwarz, Michael; Gollwitzer, Stephanie; Kasper, Burkhard S.; Lang, Johannes; Stritzelberger, Jenny; Brandner, Sebastian; Rössler, Karl; Zhao, Yining; Dörfler, Arnd; Hamer, Hajo (Journal of Neurology Neurosurgery and Psychiatry, 2024)
Background Deterioration in naming function is a common sequelae after epilepsy surgery in the language-dominant temporal lobe but information on recovery and long-term outcome is scarce. We, therefore, assessed short-term and long-term outcome of object naming in patients undergoing surgery in the temporal lobe and determined factors affecting deterioration and recovery of naming function. Method Object naming (Boston naming test) before surgery, at early follow-up (FU, 6-12 months) and late FU (≥2 years) was assessed in people with epilepsy (PWE) undergoing resections in the language-dominant left and non-dominant right temporal lobe. Results Sixty-six patients with left temporal lobe epilepsy (LTLE) and 87 control patients with right temporal lobe epilepsy (RLTE) were included. At early FU, 28 patients with LTLE (42%) and three patients with RTLE (3%) showed a significant naming decline. In patients with LTLE, risk for deterioration increased with lower verbal memory before surgery, older age at seizure onset and was particularly high with posterior temporal resections (≥40 mm from the temporal pole) and seizure onset >16 years. Of the patients with LTLE with early naming decline, 11 patients (39%) recovered fully in their naming abilities at late FU, averaging almost 10 years. Recovery was associated with the degree of postoperative naming decline at early FU. PWE with a decline of less than 10 items (<20%) had a good prognosis of recovery at late FU. Postoperative seizure control had no significant effect on recovery. Conclusions In our cohort, less than 50% of PWE showed significantly deteriorated naming function after resection of the dominant temporal lobe. If a decline occurred, it appeared to recover to a certain degree and remained as a permanent deficit in 26% of the patients. Long-term outcome of visual object naming can be predicted by the degree of early postoperative decline.
CRIS-Team Scopus Importer:2025-02-04